Hubungan Antara Ekspresi Reseptor Progesteron dengan Grade Histopatologi Meningioma di RSSA Malang - Rahmawati, Dessika; Retnani, Diah Prabawati; Damayanti, Yulia; Holifah, Holifah (PERDOSNI, 2026)
Background: Meningioma is a group of mostly benign, slow-growing neoplasms that most likely derive from meningothelial cells of the arachnoid layer of the brain and spinal medulla. Meningiomas are found in one-third of all tumors in the central nervous system. Molecular and immunohistochemical studies confirm that meningioma is a hormone-sensitive tumor, with approximately 70% of meningiomas expressing progesterone receptors and approximately 30% expressing estrogen receptors. Objective: This study aims at discovering the relationship between progesterone receptor expression and meningioma histopathological grading Methode:This study employed a cross-sectional analytical observational research design. The study sample was a paraffin block of meningioma cases at The Anatomical Pathology laboratory. The data were collected through histopathological preparations, immunohistochemical preparations, and immunohistochemical evaluation. Result:Most meningioma cases are women between 41 and 50 years. Then, it is located in the frontal part and acquired a grade of histopathology I and has a progesterone receptor expression score of 4. The chi-square test showed no significant association between progesterone receptor expression and histopathological grading of meningioma. At the same time, partial logistic regression tests showed no significant association between sex, age, and location with meningioma histopathological grading. In addition, multinomial logistic regression tests showed that the sex, age, and location did not significantly increase or decrease the risk (odds ratio) to the grade of meningioma histopathology. Conclution: This study showed no significant association between progesterone receptor expression and meningioma histopathological grading and no association between the sex, age, and location of lesions with meningioma histopathological grading